STUDY ON VARIABILITY MECHANISM OF 1997/1998 ENSO IN PACIFIC OCEAN AND EASTERN PART OF INDONESIAN ARCHIPELAGO - Luh Made Chandra; Astiti Ratnasari; I Gede Hendrawan; I Wayan Gede Astawa Karang; Yasuhiro Sugimori (BRIN, 2006)
El Nino-Southern Oscillation (ENSO) is one of the most important climate anomalies humans are concerned about. It brought many changes in physical of the ocean. This phenomenon causes changes in sea surface temperature (SST). During El-Nino condition, the SST is much warmer in eastern side of Pacific Ocean than normal condition, and during La-Nina event the SST in eastern Pacific Ocean is cooler than normal condition. From July 1997, the warm water has spread from the western Pacific Ocean towards the east and the winds in the western Pacific were blowing strongly towards the east, pushing the warm water eastward on December 1997 and January 1998. Strong La-Nina condition water extended farther westward than usual. In October 1997, during El-Nino event 1997, the SST in eastern part of Indonesia Archipelago was cooler. The varies of SST in PacificOcean during El-Nino 1997 was influenced the Indonesian Through Flow (ITF). During El-Nino event 1997, surface current flown strongly from Pacific Ocean to the Indian Ocean On the other hand, since March 1998 the surface current inversed from Indonesian Sea to the Pacific Ocean.